ANALISIS KAWASAN RAWAN GEMPA BUMI UNTUK MITIGASI BENCANA DI PALUNG SUMATRA DAN SEKITARNYA - Rosiyanti Sinaga; Imam Setiaji Ronoatmojo (Universitas trisakti, 2022)
Indonesia is situated at the junction of three active plates: Eurasia, Circum Pacific, and Indo-Australia.. Sumatran tectonics is controlled by the subduction of two plates, namely the Indo-Australian plate and the southeastern Eurasian plate. The research area is along the Sumatra Trench and the data used are from the United States Geological Survey in the last 50 years, the depth is 0-60 km, and the methodology used is the least squares method. Purpose of this study, to predict the occurrence of earthquakes with the aim of minimizing the impact of damage that occurs in earthquakes. The Locked Area has a high return period value, the influencing factor is the existence of a seismic gap, where the stress applied to this area will be isolated due to seamount subduction, so that it can withstand earthquakes. but one day, when the rock can no longer withstand the stress, it will cause an earthquake with large strength.